Strategies to Improve Employee Performance at PT. XYZ - Ary Setiawan; M. Syamsul Ma'arif; Yunus Trionggo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze strategies for improving employee performance at PT. XYZ by examining various influencing factors, including organizational culture, work environment, and work motivation. The findings indicate that organizational culture does not have a significant impact on employee performance, either directly or through the work environment as an intervening variable. In contrast, the work environment has a significant positive effect on both work motivation and employee performance. Additionally, work motivation significantly influences performance, both directly and through the work environment. Based on these results, the main recommended strategy is to enhance the company's ability to manage internal and external issues by actively involving both employees and leadership. These findings are expected to serve as a reference for policy-making and more effective human resource development at PT. XYZ.